Numerical Investigation on the Evolution of Mechanical Properties of Rock Affected by Micro-Parameters - Haoyu Rong; Guichen Li; Dongxu Liang; Changlun Sun; Suhui Zhang; Yuantian Sun (Applied Sciences, 2020)
Investigating the micro-parameters of rock is vital for understanding the macro-properties of rock, such as the uniaxial compressive strength (UCS), Young’s modulus, failure patterns, etc. In this paper, based on the experimental results of rock material, a parallel-bond model in three-dimensional particle flow code (PFC3D) was applied to investigate the effects of the joint action of bond stiffness ratio and bond stress ratio on macro-properties of rock. The uniaxial compressive strength, stress–strain relationships, and failure characteristics, as well as underlying compression and failure mechanisms, in the process of parameter calibration, were systematically studied. The results indicated that the interaction of several micro-parameters would obviously change the response characteristics of the macro-properties of the model. The mechanism of the effects of various micro-parameters on the macro-properties of the model was further revealed. The change of the micro-parameters would change the strength and stress state of the bond between particles. The research results could promote the understanding of the failure mechanism of rock and improve the efficiency of micro-parameter calibration and the accuracy of calibration results.